ANALISIS SISTEM AGRIBISNIS INDUSTRI RUMAH TANGGA TAHU DAN TEMPE (Studi kasus di Kabupaten Nganjuk) - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2000)
. .Protein is need keep increasing in arow increasion of population and income amount, while in other hand supply of protein source in Indonesia isn't enough yet. This need substitution protein source that easy to get and cheap. From WS contain, soybean with derivative product tahu and tempe is high protein source, non colesterol, contain of essential amino acid for body, easy to get and not so exspensive, where in economic crisis its demand were increasing because of instable price from other protein source